Estimating the economy-wide impacts of energy policies in Cyprus. (May 2020) - Taliotis, Constantinos; Giannakis, Elias; Karmellos, Marios; Fylaktos, Nestor; Zachariadis, Theodoros
Abstract: Decarbonisation of the global economy is necessary to achieve the climate targets set by the Paris Agreement at COP21. Significant investments are required in low-carbon technologies on the supply and demand side of energy systems; the scale of these may pose challenges to national economies. In this paper, an energy forecast model, a cost-optimisation model and an input-output model are combined to conduct an economy-wide assessment of policy pathways for energy transition in Cyprus. The results of the study indicate that a scenario with additional energy efficiency measures and a modal shift in the transport sector can reduce final energy consumption by 10% as compared to a reference case in 2030. The macroeconomic assessment shows that the measures have a moderate but positive effect on economic growth. The construction, metal products and transportation sectors are those mainly benefiting in terms of economic output generation, while the largest negative effects are observed in the energy sector. Our findings highlight the importance of targeted investments to ensure a positive impact of energy policies on the broader economy. Highlights: Energy forecast, cost-optimisation and input-output models are soft-linked A dynamic input-output model is used for macroeconomic analysis of energy policies Energy efficiency and sustainable mobility reduce overall investment requirements Lower investments and reduced energy consumption do not compromise economic growth